Pseudotyping of HIV-1 with Human T-Lymphotropic Virus 1 (HTLV-1) Envelope Glycoprotein during HIV-1–HTLV-1 Coinfection Facilitates Direct HIV-1 Infection of Female Genital Epithelial Cells: Implications for Sexual Transmission of HIV-1 - Yuyang Tang; Alvin M. George; Oksana Petrechko; Franklin J. Nouvet; Stephanie D. Sweet; Yuetsu Tanaka; Brian S. Imbiakha; Guochun Jiang; Wei Gao; Kathryn Anastos; James E. K. Hildreth (mSphere, 2018)
ABSTRACT Female genital epithelial cells cover the genital tract and provide the first line of protection against infection with sexually transmitted pathogenic viruses. These cells normally are impervious to HIV-1. We report that coinfection of cells by HIV-1 and another sexually transmitted virus, human T-lymphotropic virus 1 (HTLV-1), led to production of HIV-1 that had expanded cell tropism and was able to directly infect primary vaginal and cervical epithelial cells. HIV-1 infection of epithelial cells was blocked by neutralizing antibodies against the HTLV-1 envelope (Env) protein, indicating that the infection was mediated through HTLV-1 Env pseudotyping of HIV-1. Active replication of HIV-1 in epithelial cells was demonstrated by inhibition with anti-HIV-1 drugs. We demonstrated that HIV-1 derived from peripheral blood of HIV-1–HTLV-1-coinfected subjects could infect primary epithelial cells in an HTLV-1 Env-dependent manner. HIV-1 from subjects infected with HIV-1 alone was not able to infect epithelial cells. These results indicate that pseudotyping of HIV-1 with HTLV-1 Env can occur in vivo. Our data further reveal that active replication of both HTLV-1 and HIV-1 is required for production of pseudotyped HIV-1. Our findings indicate that pseudotyping of HIV-1 with HTLV-1 Env in coinfected cells enabled HIV-1 to directly infect nonpermissive female genital epithelial cells. This phenomenon may represent a risk factor for enhanced sexual transmission of HIV-1 in regions where virus coinfection is common. IMPORTANCE Young women in certain regions of the world are at very high risk of acquiring HIV-1, and there is an urgent need to identify the factors that promote HIV-1 transmission. HIV-1 infection is frequently accompanied by infection with other pathogenic viruses. We demonstrate that coinfection of cells by HIV-1 and HTLV-1 can lead to production of HIV-1 pseudotyped with HTLV-1 Env that is able to directly infect female genital epithelial cells both in vitro and ex vivo. Given the function of these epithelial cells as genital mucosal barriers to pathogenic virus transmission, the ability of HIV-1 pseudotyped with HTLV-1 Env to directly infect female genital epithelial cells represents a possible factor for increased risk of sexual transmission of HIV-1. This mechanism could be especially impactful in settings such as Sub-Saharan Africa and South America, where HIV-1 and HTLV-1 are both highly prevalent.